¿EN COLOMBIA SE RESPETA EL PRINCIPIO NON BIS IN ÍDEM? (2016)
The absolute character of the non bis in idem principle might be subject to a further debate, as both, the jurisdiction and the government administration are granted faculties in order to sanction fellow citizens, therefore there is an undeniable possibility to try and/or sanction the same person based on the same facts on different legal regimes, which at first sight might end up breaching the non bis in idem.The Colombian jurisdictional regime doesn’t escape from this legal contingency either. It’s precisely the contingency the main reason of doing this essay in order to understand whether the non bis in idem principle is being respected under the national legal framework, particularly the administrative law penalties. To fulfill this academic objective, it is vital to do a conceptual, historical and comparative approximation of the non bis in idem that allows to project it within the described quandary of investigations and sanctions.